2013
DOI: 10.1016/j.fuel.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and emissions characteristics of a dual fuel engine operated on alternative gaseous fuels

Abstract: Among the different efforts towards the reduction in pollutant emissions from direct injection (DI) diesel engines, the use of gaseous fuels as a partial supplement for diesel fuel has been proposed by many researchers. These engines are known as dual fuel engines. An experimental investigation was performed to investigate the influence of dual-fuel combustion on the performance and exhaust emissions of a DI diesel engine fueled with natural gas (NG) and biogas. In this work, the combustion pressure and the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(69 citation statements)
references
References 44 publications
(60 reference statements)
3
51
0
5
Order By: Relevance
“…Feroskhan and Ismail [77] used simulated biogas and reported that methane enrichment will enhance the brake thermal efficiency at low biogas flow rates. Mustafi et al [64] also observed that the brake specific energy consumption of the biogas-diesel dual fuel and diesel-only modes was nearly the same. Sorathia and Yadav [78] also reported almost no deterioration in brake thermal efficiency in a CI engine operated in dual fuel mode with diesel and biogas.…”
Section: Performance Indicesmentioning
confidence: 91%
See 3 more Smart Citations
“…Feroskhan and Ismail [77] used simulated biogas and reported that methane enrichment will enhance the brake thermal efficiency at low biogas flow rates. Mustafi et al [64] also observed that the brake specific energy consumption of the biogas-diesel dual fuel and diesel-only modes was nearly the same. Sorathia and Yadav [78] also reported almost no deterioration in brake thermal efficiency in a CI engine operated in dual fuel mode with diesel and biogas.…”
Section: Performance Indicesmentioning
confidence: 91%
“…Studies on an IDI engine with biogas in dual fuel mode with diesel substitution up to 48% indicated a reduction in combustion duration and consequently lower exhaust gas temperatures [58]. In a study involving biogas-diesel dual fuel operation, the maximum Net Heat Release Rate (NHRR) was observed to be around 30% greater for the dual fuel mode compared to diesel-only mode under similar loading and speed conditions [64]. The increase in ID can be offset by using higher quantity of pilot fuel.…”
Section: Combustion Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…This trend could be ascribed to the methane presence that lowers the temperature in the chamber thus inhibiting the diesel ignition in DF operation. The longer diesel ignition delay in DF mode could also be ascribed to chemical factors: the methane mixed with air, in fact, alters the properties of the charge, the oxygen concentration and the pre-ignition reaction activities during compression [11].…”
Section: S583mentioning
confidence: 99%